Pathological Neuroinflammatory Conversion of Reactive Astrocytes Is Induced by Microglia and Involves Chromatin Remodeling - Villarreal, Alejandro; Vidos, Camila; Monteverde Busso, Matías; Cieri, María Belén; Ramos, Alberto Javier (Frontiers in Pharmacology, 2021)
Following brain injury or in neurodegenerative diseases, astrocytes become reactive and may suffer pathological remodeling, features of which are the loss of their homeostatic functions and a pro-inflammatory gain of function that facilitates neurodegeneration. Pharmacological intervention to modulate this astroglial response and neuroinflammation is an interesting new therapeutic research strategy, but it still requires a deeper understanding of the underlying cellular and molecular mechanisms of the phenomenon. Based on the known microglial–astroglial interaction, the prominent role of the nuclear factor kappa B (NF-κB) pathway in mediating astroglial pathological pro-inflammatory gain of function, and its ability to recruit chromatin-remodeling enzymes, we first explored the microglial role in the initiation of astroglial pro-inflammatory conversion and then monitored the progression of epigenetic changes in the astrocytic chromatin. Different configurations of primary glial culture were used to modulate microglia–astrocyte crosstalk while inducing pro-inflammatory gain of function by lipopolysaccharide (LPS) exposure. In vivo, brain ischemia by cortical devascularization (pial disruption) was performed to verify the presence of epigenetic marks in reactive astrocytes. Our results showed that 1) microglia is required to initiate the pathological conversion of astrocytes by triggering the NF-κB signaling pathway; 2) this interaction is mediated by soluble factors and induces stable astroglial phenotypic changes; 3) the pathological conversion promotes chromatin remodeling with stable increase in H3K9K14ac, temporary increase in H3K27ac, and temporary reduction in heterochromatin mark H3K9me3; and 4) in vivo reactive astrocytes show increased H3K27ac mark in the neuroinflammatory milieu from the ischemic penumbra. Our findings indicate that astroglial pathological pro-inflammatory gain of function is associated with profound changes in the configuration of astrocytic chromatin, which in turn are initiated by microglia-derived cues. These results open a new avenue in the study of potential pharmacological interventions that modify the initiation and stabilization of astroglial pathological remodeling, which would be useful in acute and chronic CNS injury. Epigenetic changes represent a plausible pharmacological target to interfere with the stabilization of the pathological astroglial phenotype.